Phylogenetics, biogeography and character evolution in the Ornithocephalus clade (Orchidaceae, Oncidiinae) - Smidt, Eric C.; Toscano De Brito, A. L. V.; Martins, Aline C.; Royer, Carla A. [UNESP]; Whitten, W. Mark; Chase, Mark W. (Oxford Univ Press, 2018)
The Ornithocephalus clade (OC) consists of small, epiphytic orchids from the Neotropics. Thirty-six species of the OC and ten outgroup taxa were investigated using nrITS sequences analysed using maximum parsimony, maximum likelihood and Bayesian inference. Molecular dating, biogeographical analyses and character reconstruction were also performed. Our results show a well-supported topology that agrees with all current generic circumscriptions, and complete congruence among the different phylogenetic methods. Based on a molecular clock analysis, the OC originated in the Miocene c. 10 (6-14) Mya and all genera were established by the Pliocene at 3.5 (1.8-5.6) Mya. The biogeographic reconstruction shows an origin and early diversification of the OC in the Atlantic Forest (Morrone's Parana province), where six out of ten genera are restricted today. Only five of the 13 morphological characters reconstructed could be identified as unambiguous apomorphies for some genera, and a number of characters were ambiguous in the last common ancestor of the OC. The findings from this study provide a first broad phylogenetic hypothesis supporting generic circumscription and relationships in the OC and clarifying their origin and biogeographical history. Reconstruction of important morphological characters shows high plasticity in pseudobulb presence and multiple origins of asymmetric flowers. The column is the organ with the highest homology issues and further studies are needed to understand the origin of its various appendages and the tabula infrastigmatica.
Keywords: Atlantic Forest; biogeography; character evolution; molecular phylogenetics; nrITS; Neotropics